The Financial Stability in Developing Economy: Role of Financial Inclusion and Financial Efficiency - Rahman Olanrewaju Raji (Quantitative Economics and Management Studies, 2021)
This paper explores the asymmetric nexus between financial inclusion, financial efficiency and financial stability, within asymmetric and symmetric Autoregressive Distributed Lag (NARDL) framework, covering the period from 2003 to 2018, using quarterly data in Nigeria. The findings showed that symmetric technique of econometric test detects, that financial stability is augmented by better improvement in financial inclusion in short-run, while asymmetric technique observed that short-run positive effect, and negative effect likewise long-run decrease in this index heightened the level of financial stability in this economy. This study further found trade-off existence, between financial efficiency and financial stability in both symmetric and asymmetric techniques of econometric tests, which is consistent with some empirical findings. The results based on the model and empirical data indicate that, the monetary authority needs to follow prudent and adequate supervisory standard in pursuing financial inclusion, financial intermediaries should be accompanied with good institutional quality, including financial awareness that should be enhanced through financial teachings in all sectors both in the urban and rural areas of the economy.